Molecular structure and absolute configuration of tatridin a and b from Lepidolopha karatavica - Turdybekov, K. M.; Morozova, O.A.; Ivasenko, S.A.; Makhmutova, A.S.; Turdybekov, D.M.; Adekenov, S.M. (Chemistry of Natural Compounds, 2021)
The germacrane-type sesquiterpene lactones tatridin A and B were isolated for the first time during chemical studies of the extract of Lepidolopha karatavica. The structures of the compounds were elucidated using spectral data and X-ray crystal structure analyses (XSAs). Correlations of the XSAs and CD spectra defined the absolute configurations of the molecules. Possible conformational states of 3,8-deoxytatridin A and B were calculated by a quantum chemical method
Keywords: sesquiterpene lactones; Lepidolopha karatavica; crystal structure; NMR; XSA; molecular conformation